Structure of Knowledge in the Early Texts of Prajñāparamitā - Коробов, Владимир (Acta Orientalia Vilnensia, 2000)
The structure of nitārtha knowledge as it is exposed in the text of Abhisamayālankāra–prajñāpāramitā—upadeśaśāstra (A. A.) may be represented as a succession of forms of consciousness topologically coincided with the text itself. The knowledge may be interpreted as a particular order of recollection of dharmas (phenomenоn, words). In this context the problem of deliverance is associated with substitutiono of defiled sansaric text with the text made of pure unconditioned elements.